Analisis Akuntansi Kombinasi Bisnis Dengan Konvergensi Ifrs Pada Laporan Keuangan PT Garuda Indonesia Persero (Tbk) - Ranaa Naziira Givasya Anggoro; Natasya Alveenia; Agustine Dwianika (Populer: Jurnal Penelitian Mahasiswa, 2023)
This study aims to analyze business combination accounting with IFRS convergence in the financial statements of PT Garuda Indonesia Persero (Tbk). The research method used in this research is qualitative method, with content analysis as the data analysis technique. This research is based on the results of a review of the PT Garuda Indonesia Persero (Tbk) financial statement in 2010, 2011, 2015 and 2018, which were taken from the company's official website. The results of the study show that PT Garuda Indonesia Persero (Tbk) has complied in applying the PSAK 22 business combination accounting standards (revisions 2010, 2015 and 2018) which have converged well with IFRS in its financial statements. This research can provide an important contribution for the stakeholders to assess company compliance with applicable accounting reporting standards.